Pengembangan Agribisnis Unggulan Dalam Upaya Penanggulangan Kemiskinan Di Propinsi Aceh - Akhmad Baihaqi; A. Humam Hamid (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. Aceh province is a potential area of agricultural resources. This resource is the main livelihood in rural communities. The low income of farmers and resulted in the inability of agricultural management resulted in the magnitude of the farming community who are in poverty. This study aims to provide models of agribusiness development to reduction of poverty in Aceh. The results of review provide an indication of the factors that support poverty in the farming community is the lack of tried ability and creativity, lack of education and skills and lack of access to capital and land availability. Measures to reduce poverty in the agricultural sector can be done with agribusiness development upstream-downstream, to strengthen the partnership of farmers and groups, partnership groups and entrepreneurs (market access), improving skills match the needs and based on local resources, create and develop regional integrated agribusiness based on local resources.